Cartography and spatial distribution of the genus Pistacia in Souk Ahras, Northeast Algeria (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Barour AA. 2021. Cartography and spatial distribution of the genus Pistacia in Souk Ahras, Northeast Algeria. Biodiversitas 23: 286-290. In 2020, a study mapped two species of the genus Pistacia, viz. Pistacia atlantica Desf. and Pistacia vera L. in the Wilaya of Souk Ahras situated in the northeast of Algeria. The study was based on the determination of the geographic coordinates of each individual and mapping their spatial distribution by using MapInfo Pro 12.0.2 software. The results showed that Atlas Pistachio was mainly distributed over four localities viz. Batoum, Ben Attia, Sidi Fredj and Ouled Moumen. However, the Pistachio nut species were distributed over two localities in the south of the Wilaya of Souk Ahras, viz. Ben Attia and Sidi Fredj. The locality of Ben Attia was characterized by a more or less random distribution of trees, mostly young plants. At thr same time, the structure was heterogeneous across the other stations, with the dominance of large and old trees. The spacing between the trees of the Atlas Pistachio varied from one region to another, ranging from 3 to 189 m. At the Ouled Moumen area, the distribution of wild Pistachio trees formed circles with very close distances between neighboring feet. On the other hand, the trees were spaced and distributed in a linear manner across the other stations.